Coenzyme A-acylating aldehyde dehydrogenase from Clostridium beijerinckii NRRL B592. - Yan, R T (1990)
Acetaldehyde and butyraldehyde are substrates for alcohol dehydrogenase in the production of ethanol and 1-butanol by solvent-producing clostridia. A coenzyme A (CoA)-acylating aldehyde dehydrogenase (ALDH), which also converts acyl-CoA to aldehyde and CoA, has been purified under anaerobic conditions from Clostridium beijerinckii NRRL B592. The ALDH showed a native molecular weight (Mr) of 100,000 and a subunit Mr of 55,000, suggesting that ALDH is dimeric. Purified ALDH contained no alcohol dehydrogenase activity. Activities measured with acetaldehyde and butyraldehyde as alternative substrates were copurified, indicating that the same ALDH can catalyze the formation of both aldehydes for ethanol and butanol production. Based on the Km and Vmax values for acetyl-CoA and butyryl-CoA, ALDH was more effective for the production of butyraldehyde than for acetaldehyde. ALDH could use either NAD(H) or NADP(H) as the coenzyme, but the Km for NAD(H) was much lower than that for NADP(H). Kinetic data suggest a ping-pong mechanism for the reaction. ALDH was more stable in Tris buffer than in phosphate buffer. The apparent optimum pH was between 6.5 and 7 for the forward reaction (the physiological direction; aldehyde forming), and it was 9.5 or higher for the reverse reaction (acyl-CoA forming). The ratio of NAD(H)/NADP(H)-linked activities increased with decreasing pH. ALDH was O2 sensitive, but it could be protected against O2 inactivation by dithiothreitol. The O2-inactivated enzyme could be reactivated by incubating the enzyme with CoA in the presence or absence of dithiothreitol prior to assay.